Sequence variability in four mitochondrial genes among rabbit pinworm (Passalurus ambiguus) isolates from different localities in China. (August 2015) - Sheng, Li; Cui, Ping; Fang, Su-Fang; Lin, Rui-Qing; Zou, Feng-Cai; Zhu, Xing-Quan
Abstract Passalurus ambiguus is a common pinworm which parasitizes in the caecum and colon of rabbits. This study examined genetic variability among P. ambiguus isolated from naturally infected rabbits in four different provinces in China. The partial mitochondrial (mt) cytochrome c oxidase subunit 1 (pcox1), cytochrome b (pcytb) and NADH dehydrogenase subunits 1 and 5 (pnad1 and pnad5) were amplified separately from individual nematodes by PCR and sequenced. The results showed that pcox1, pcytb, pnad1 and pnad5 were 714, 663, 645 and 546 bp in length, respectively. The intra-specific sequence variations within P. ambiguus were 0–1.1% for pcox1, 0–1.2% for pcytb, 0–0.6% for pnad1 and 0–1.3% for pnad5, whereas inter-specific sequence differences with other members of the Oxyuridae were 16.2–17.3% for pcox1, 27.8–30.4% for pcytb, 20.2–24.0% for pnad1 and 27.1–30.3% for pnad5. Phylogenetic analyses using Bayesian inference (BI), maximum likelihood (ML) and maximum parsimony (MP) methods, based on the combined sequences of the four partial mtDNA sequences, revealed that all the P. ambiguus samples form monophyletic groups. This study demonstrated the existence of low-level intra-specific variation in cox1, cytb, nad1 and nad5 genes among P. ambiguus isolates from different geographic regions in China, and these four mtDNA sequences can be used as genetic markers for the population genetic studies of P. ambiguus, as well as the differentiation of P. ambiguus from other oxyurid nematodes.